Pengaruh Flash Sale, Gratis Ongkos Kirim, dan Live Streaming terhadap Impulsive Buying pada pengguna Shopee - Rizkya, Susi Nurul; Sarah, Siti; Fanji, Fanji Wijaya (Training & Research Institute - Jeramba Ilmu Sukses, 2024)
The development of the internet and technological advancements have significantly altered the way individuals engage in various activities. Shop, facilitate consumer activities, and create consumptive behavior patterns among Indonesians. It is shown in the increasing use of e-commerce in Indonesia. The advancement of time and internet technology has significantly changed how the general public lives. The increasingly advanced internet has provided great convenience in everyday life, particularly in the corporate world. These days, information and communication technology forms the basis of brand promotion., market expansion, and the transaction and purchase process through e-commerce platforms. OECD in 2019 defines E-commerce as the term used to describe the practice of purchasing and selling goods and services over the internet., with a special system for transactions and orders. This can happen between individuals, households, government agencies, and private or public organizations. This change makes it easy for consumers to get goods without moving from the place and saves time. This change also reflects the global shift from conventional marketing (offline) to digital marketing (online). Marketing strategies implemented by many companies have great potential to provide product information and facilitate the transaction process through Internet platforms. This study attempts to determine how Shopee users' impulsive purchases are affected by flash deals, free shipping, and live streaming. The research methodology employed in this study makes use of questionnaire-based research data. Hypothesis testing was used to investigate the associations between several independent factors and a dependent variable, and multiple linear regression analysis was used. To determine partially and simultaneously. Analysis was done on how the independent variable affected the dependent variable at a 95% confidence level (α = 0.05). This is done through the F-test and t-test. Flash Sales, Free Shipping, and Live Streaming against impulsive buying in Shopee users are the objects of this study. There were one hundred customers in the sample used in this investigation. The findings of this study partially Flash Sale affects impulsive buying in shop users. Partial free shipping influences impulsive buying in Shopee users. Partially, live streaming affects the impact